Metabolic characteristics of women with polycystic ovaries and oligo-amenorrhoea but normal androgen levels: implications for the management of polycystic ovary syndrome. - Barber, T; Wass, J; McCarthy, M; Franks, S (2007)
OBJECTIVE: Application of the newly introduced Rotterdam criteria for polycystic ovary syndrome (PCOS) generates four phenotypic subgroups, defined by the presence/absence of three diagnostic elements: polycystic ovarian (PCO) morphology (P); hyperandrogenism (H); and oligo-amenorrhoea (O). Whilst PCOS is associated with adverse metabolic features, the strength of the association within individual subgroups is not established. We characterized the metabolic and endocrine profiles of PCOS women who are oligomenorrhoeic but normoandrogenaemic, and compared these to other PCOS women and controls. DESIGN: Retrospective dataset analyses. PATIENTS: A total of 309 Europid PCOS women, all with PCO morphology, of whom 191 were also hyperandrogenaemic and oligomenorrhoeic (PHO), 76 hyperandrogenaemic with normal menses (PH) and 42 oligomenorrhoeic but normoandrogenaemic (PO); plus 76 Europid control women without PCOS. MEASUREMENTS: Metabolic parameters: fasting insulin, lipids, homeostasis model assessment (HOMA) measures of insulin sensitivity; endocrine variables: LH, FSH; prevalence of metabolic syndrome. RESULTS: Insulin sensitivity: PO women were indistinguishable from controls, and markedly less insulin-resistant than PHO women (vs. controls, P = 0.38 after adjustment for BMI and age; vs. PHO, P = 0.003). Metabolic syndrome: the prevalence in PO women (7.1%) was similar to that in controls (3.9%), and lower than in PHO women (29.3%, P < 0.0001). LH levels: PO women were intermediate between controls (vs. controls, P = 0.008) and PHO women (vs. PHO, P = 0.06). CONCLUSIONS: Normoandrogenaemic, oligomenorrhoeic women with PCOS are metabolically similar to control women with significantly fewer metabolic features than PCOS women who are also hyperandrogenaemic. However, higher than normal LH and lower sex hormone-binding globulin (SHBG) concentrations in the PO women support the view that they form part of the spectrum of PCOS.